Mushroom Ganoderma lucidum Prevents Colitis-Associated Carcinogenesis in Mice - Sliva, Daniel; Loganathan, Jagadish; Jiang, Jiahua; Jedinak, Andrej; Lamb, John G.; Terry, Colin; Baldridge, Lee Ann; Adamec, Jiri; Sandusky, George E.; Dudhgaonkar, Shailesh (PLOS ONE, 2012)
Background Epidemiological studies suggest that mushroom intake is inversely correlated with gastric, gastrointestinal and breast cancers. We have recently demonstrated anticancer and anti-inflammatory activity of triterpene extract isolated from mushroom Ganoderma lucidum (GLT). The aim of the present study was to evaluate whether GLT prevents colitis-associated carcinogenesis in mice. Methods/Principal Findings Colon carcinogenesis was induced by the food-borne carcinogen (2-Amino-1-methyl-6-phenylimidazol[4,5-b]pyridine [PhIP]) and inflammation (dextran sodium sulfate [DSS]) in mice. Mice were treated with 0, 100, 300 and 500 mg GLT/kg of body weight 3 times per week for 4 months. Cell proliferation, expression of cyclin D1 and COX-2 and macrophage infiltration was assessed by immunohistochemistry. The effect of GLT on XRE/AhR, PXR and rPXR was evaluated by the reporter gene assays. Expression of metabolizing enzymes CYP1A2, CYP3A1 and CYP3A4 in colon tissue was determined by immunohistochemistry. GLT treatment significantly suppressed focal hyperplasia, aberrant crypt foci (ACF) formation and tumor formation in mice exposed to PhIP/DSS. The anti-proliferative effects of GLT were further confirmed by the decreased staining with Ki-67 in colon tissues. PhIP/DSS-induced colon inflammation was demonstrated by the significant shortening of the large intestine and macrophage infiltrations, whereas GLT treatment prevented the shortening of colon lengths, and reduced infiltration of macrophages in colon tissue. GLT treatment also significantly down-regulated PhIP/DSS-dependent expression of cyclin D1, COX-2, CYP1A2 and CYP3A4 in colon tissue. Conclusions Our data suggest that GLT could be considered as an alternative dietary approach for the prevention of colitis-associated cancer.